Diffraction effects in the Recoil-Frame Photoelectron Angular Distributions of Halomethanes. (August 2015) - Bomme, Cédric; Anielski, Denis; Savelyev, Evgeny; Boll, Rebecca; Erk, Benjamin; Bari, Sadia; Viefhaus, Jens; Stener, Mauro; Decleva, Piero; Rolles, Daniel
Synopsis: We have measured the Recoil Frame - Photoelectron Angular Distributions (RF-PADs) for inner-shell photoionization of CH3 F, CH3 I and CF3 I halomethane molecules for photoelectron energies up to 300 eV detected within a 4 π solid angle in the gas-phase. For high kinetic energies, the RF-PADs are dominated by diffraction effects that encode information on the molecular geometry.